Tubulointerstitial nephritis antigen‐like 1 deficiency alleviates age‐dependent depressed ovulation associated with ovarian collagen deposition in mice - Akaiwa, Masato (Reprod Med Biol, 2019)
PURPOSE: This study aimed to examine whether the Tinagl1 might be associated with ovulation in aged females and reproductive age‐associated fibrosis in the stroma of the ovary. METHODS: To address the ovulatory ability and quality of ovulated oocytes, we induced ovulation by treatment with equine chorionic gonadotropin (eCG) and human chorionic gonadotropin (hCG) followed by in vitro fertilization. We also performed Picrosirius Red (PSR) staining to evaluate ovarian collagen deposition. RESULTS: As compared to ovulation in 8‐ to 9‐month‐old Tinagl1(flox/flox) mice, the number of ovulated oocytes from Tinagl1(flox/flox) mice decreased in an age‐dependent manner in mice more than 10‐11 months old, whereas the ovulated oocyte numbers in Tinagl1 (−/−) mice decreased significantly at 14‐15 months. In vitro fertilization followed by embryo culture demonstrated the normal developmental potential of Tinagl1‐null embryos during the preimplantation period. PSR staining indicated that collagen was found throughout the ovarian stroma in an age‐dependent manner in Tinagl1(flox/flox) females, whereas those distributions were delayed to 14‐15 months in Tinagl1 (−/−) females. This timing was consistent with the delayed timing of age‐related decline of ovulation in Tinagl1 (−/−) females. CONCLUSIONS: The alleviation of age‐associated depression of ovulation was caused by delayed ovarian collagen deposition in Tinagl1‐null female mice.